2022
DOI: 10.1021/jacs.2c01884
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Fueled Active Supramolecular Materials

Abstract: Fuel-driven dissipative self-assemblies play essential roles in living systems, contributing both to their complex, dynamic structures and emergent functions. Several dissipative supramolecular materials have been created using chemicals or light as fuel. However, electrical energy, one of the most common energy sources, has remained unexplored for such purposes. Here, we demonstrate a new platform for creating active supramolecular materials using electrically fueled dissipative self-assembly. Through an elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 43 publications
1
60
1
Order By: Relevance
“…The ultrasensitive response of the coacervates in our work is attributable to the competition of the reactive radicals between the methacrylate monomer and molecular oxygen. , As described above, molecular oxygen diffused from the air effectively quenches reactive radical species at a lower frequency to generate a threshold, whereas the amount of the radicals produced at a higher frequency becomes higher than that of molecular oxygen to proceed radical polymerization, resulting in the ultrasensitive response. Such an ultrasensitive response based on the competitive mechanism is considered as a new example of light-fueled dissipative systems. , To date, it has been reported that coacervates can provide a microenvironment to accelerate catalytic reactions mainly through molecular sequestration , and to realize stimulus responses towards reactive molecules ( e.g. , assembly–disassembly). ,,,,, Compared with these examples, one of the important aspects of our work is to combine the rate enhancement effect with competitive inhibition via continuous supply of diffusing O 2 , which establishes a unique system in response to temporally distinct stimulus patterns.…”
Section: Resultsmentioning
confidence: 99%
“…The ultrasensitive response of the coacervates in our work is attributable to the competition of the reactive radicals between the methacrylate monomer and molecular oxygen. , As described above, molecular oxygen diffused from the air effectively quenches reactive radical species at a lower frequency to generate a threshold, whereas the amount of the radicals produced at a higher frequency becomes higher than that of molecular oxygen to proceed radical polymerization, resulting in the ultrasensitive response. Such an ultrasensitive response based on the competitive mechanism is considered as a new example of light-fueled dissipative systems. , To date, it has been reported that coacervates can provide a microenvironment to accelerate catalytic reactions mainly through molecular sequestration , and to realize stimulus responses towards reactive molecules ( e.g. , assembly–disassembly). ,,,,, Compared with these examples, one of the important aspects of our work is to combine the rate enhancement effect with competitive inhibition via continuous supply of diffusing O 2 , which establishes a unique system in response to temporally distinct stimulus patterns.…”
Section: Resultsmentioning
confidence: 99%
“…[62,63] Besides molecular machines, the same strategy might be used to operate non-equilibrium supramolecular systems that rely on electrical energy, such as fiber-forming monomers. [37,41] Implementing the autonomous use of electrical energy by supramolecular assemblies to perform molecular motions advances our ability to control matter away from equilibrium. [9,64]…”
Section: Discussionmentioning
confidence: 99%
“…Efforts in this direction were recently reported in relation to the selfassembly of a cysteine derivative, which was modulated by controlling the potential of an electrode in the presence of a homogeneous reducing agent, leading to fibers formation under nonequilibrium conditions. [37] To address the outlined challenge, one possibility is to rely on redox-active oscillating systems, where the origin of the emergent phenomena is rooted in the kinetic control of redox reactions. Albeit prominent examples have been reported, [38][39][40][41] this approach suffers from limited flexibility and it is difficult to generalize since it critically relies on specific kinetic features of the oscillating system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts in the past decade to mimic such out-of-equilibrium control in constructing molecular assemblies have yielded various forms of synthetic dissipative materials. Pioneering works in this area have demonstrated molecular assemblies driven by chemical reaction networks where the added fuel converts a precursor into an assembling or a disassembling species and a spontaneous chemical process (e.g., hydrolysis) reverts it to the precursor state. In these systems, the chemical energy in the fuel temporarily produces a transient metastable species, while the fuel is converted into waste. Other forms of energy to generate metastable states, including light, and more recently, electricity, have been introduced to construct and control dissipative materials.…”
Section: Introductionmentioning
confidence: 99%